The Effect of Father's Education on Increasing Knowledge, Attitudes, and Practice of Health Protocols in Preventing COVID-19 in Nursing Students - Sarma Eko Natalia Sinaga (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims : This study aims to determine the effect of father's education on increasing knowledge, attitudes, the practice of health protocols in preventing COVID-19 in nursing students. Design : This study is a quantitative study using the pre-experimental with one-group pretest-posttest design Methods : The data was collected through questionnaire which distributed on Google Form to the 166 respondents. The intervention is to provide health education to respondents via the internet: Windows 365 (Teams) about information and ways to prevent COVID-19, as well as simulations on how to wash hands, physical distancing, and dispose of masks which are carried out in 2 sessions in 1 week.  Results : The results showed that the number of fathers of nursing students with low education was 134 (80.7%), while the fathers of nursing students with higher education were 32 (19.3%). Meanwhile, the statistical test results obtained a p-value of 0.000 which indicates that there is a significant difference between knowledge about COVID-19, health protocol attitudes, and respondents with low father education and high father education before and after the intervention. Conclusions : There was increase in knowledge, attitude and practice of health protocol for nursing students in avarage after they got education. COVID-19 is very important for nursing students to learn about in order to improve their knowledge, attitudes, and practice of health protocols so that COVID-19 does not happen.